Umbrella clauses and autonomy regulation: assessing the impact on indonesia's regulatory capability for the public interest - Nindyatsyah (The International Journal of Politics and Sociology Research, 2023)
Foreign Direct Investment (FDI) plays a key role in the contemporary global economy. The Bilateral Investment Treaty (BITs) guarantees equitable treatment in Investment Arbitration and Contractual Commitments, despite the divergent goals of the home and host countries involved. The emergence of certain events gave rise to a conflict resolution issue, which subsequently led to the implementation of an umbrella clause aimed at safeguarding investments associated with contract violations. The "Umbrella Clause" is a contentious legal provision commonly included in bilateral investment treaties (BITs) and international investment agreements (IIAs), which significantly impacts the regulatory autonomy of a host state. The primary objective of this process is to convert the contractual obligations established between foreign investors and host countries into legally binding commitments within the framework of the treaty. However, many foreign investors utilize this clause to circumvent government regulations in the host country. The primary objectives of this research is the to establish a thorough comprehension of the effects that the Umbrella Clause has on regulatory sovereignty in Indonesia; to assess the viability of including scope reform clauses in future BITs and IIAs to reconcile investment protection with the state's right to regulate in the public interest; and to mitigate any potential negative consequences that may arise from the Umbrella Clause's application on regulatory autonomy.